2001
DOI: 10.1111/0022-1082.00408
|View full text |Cite
|
Sign up to set email alerts
|

A Rose.com by Any Other Name

Abstract: We document a striking positive stock price reaction to the announcement of corporate name changes to Internet-related dotcom names. This "dotcom" effect produces cumulative abnormal returns on the order of 74 percent for the 10 days surrounding the announcement day. The effect does not appear to be transitory; there is no evidence of a postannouncement negative drift. The announcement day effect is also similar across all firms, regardless of the firm's level of involvement with the Internet. A mere associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
261
5
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(300 citation statements)
references
References 9 publications
15
261
5
1
Order By: Relevance
“…One of the works found that some investors cannot process new information correctly and so overreact to new information (Werner et al, 1986). What is worse, information which investors overreact to is unconfirmed (Bloomfield et al, 2000) or unreliable (Pound and Zeckhauser, 1990;Tumarkin and Whitelaw, 2001) or even unimportant (Rashes, 2001;Cooper et al, 2001). Also, investors who consult experts may not get much helpful advice since security analysts tend to be overoptimistic (Dechow et al, 2000) and having conflict of interest (Cowen et al, 2006).…”
Section: Strategymentioning
confidence: 99%
“…One of the works found that some investors cannot process new information correctly and so overreact to new information (Werner et al, 1986). What is worse, information which investors overreact to is unconfirmed (Bloomfield et al, 2000) or unreliable (Pound and Zeckhauser, 1990;Tumarkin and Whitelaw, 2001) or even unimportant (Rashes, 2001;Cooper et al, 2001). Also, investors who consult experts may not get much helpful advice since security analysts tend to be overoptimistic (Dechow et al, 2000) and having conflict of interest (Cowen et al, 2006).…”
Section: Strategymentioning
confidence: 99%
“…While the event study methodology is applied studies of the protest effect, it is also used extensively in the financial and economic literature. Examples of such studies include Johnson, Kasznik, and Nelson (2000), Carow and Heron (2002), Carow and Kane (2002), and Howe and Jain (2004) on the effect of legislation on investors' wealth; the works of Schwert (1981), Henry (2000), and Jackson and Madura (2007) on the effects of regulations and liberalization on stock performance; research by Cooper, Dimitrov, and Raghavendra Rau (2001) on the effect of company change of name on its stock returns; Chen and Siems (2004) on the effect of terrorism; and works by Berman, Brooks, and Davidson (2000) and Veraros, Kasimati, and Dawson (2004) on the effect of major sports events. This list, of course, is not exhaustive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cooper et al (2001) also report a pre-event rise in prices for their sample. Excess returns are almost 24% on the pick day and -24% in the following 10 days.…”
Section: A Activity and Liquidity Before And After The Pick Day: Allmentioning
confidence: 99%
“…Huberman and Regev (2001) show that prominent news of a cancer-curing drug, although previously published, had a massive, long-lasting impact on the drug company stocks. Cooper, Dimitrov and Rau (2001) find dramatic price increases following corporate name changes to Internet-related dotcom names, independent of the firm's level of involvement with the Internet. Rashes (2001) documents the comovement of stocks with similar ticker symbols.…”
mentioning
confidence: 94%